Managing Narankg Kampongk Ritual Ceremonies by Salako community customary leaders in preserving culture of Sarawak ethnic - Hanis, Hazizy; Abg Shokeran, Dyg Hadzlina Quintan; Adam Assim, Mohamad Ibrani Shahrimin; Anak Jawan, Jayum; Abg Shokeran, Abang Lukmanurhakim Bin (Human Resources Management Academic Research Society (HRMARS), 2023)
Unique and invaluable artefacts of Sarawak culture are facing extinction due to lack of qualitative documentations and scientific explorations. Salako community in the rural of Sarawak posed the serious need to sustain such unique cultures. With the culture and the belief system of Salako community which has been handed down from generation to generation without any written sources, also known as anan’ baketab, vast sociocultural changes are happening drastically. Nonetheless, the village chief plays an important role to ensure the culture of Salako community remains sustainable. The purpose of this paper is to serve as a source of reference in regard to the culture of the Salako community. The focus of the investigation was to examine the role of Salako traditional leaders and the pre-event, during-event, and post-event management of the Narankg Kampongk of the Salako community as a process of cultural preservation. This study employed ethnographic methods for data collection by using an ethnographic interview technique that involves the informants who are experts on Narankg Kampongk ritual ceremony, who are known as Binua and Tuha Adat. In addition, observation methods are also widely used in this research to deeply understand the ritual ceremonies of Narankg Kampongk in the village of Salako community around Sematan, Lundu, Sarawak. The findings indicate that the village chief of Salako community practices numerous specific and unique elements of management within their ritual ceremonies which include proper planning, organization, leadership, education, co-ordination, and regulation.